Language learner strategies : contexts, issues and applications in second language learning and teaching - Grenfell, Michael, 1953-; Harris, Vee, 1949- (Bloomsbury Academic, 2017)
"Language Learner Strategies combines principles with research and classroom practice, providing a new view of language learning to inform policy and teaching methodology. Divided into three parts, the book draws links between language learning theory in the established research literature, the authors' own empirical studies and the implications for curriculum policy and teacher education. The book addresses issues that to date have not been fully explored including the strategies of the 12-15 year old age range learning Modern Languages such as French, German, Spanish and Mandarin Chinese. A special focus is given to the sociocultural aspects of learner strategies and their link with psychological contexts in which they are used. The authors explore the cognitive turn in language learner strategy research and the practical teaching approaches it helps to develop. It sets a future agenda for learner strategy research and classroom practice."--Bloomsbury Publishing